Abuso do direito de voto do acionista controlador nas sociedades anônimas de capital aberto - Esperandio, Eduarda Exposto (2019)
The objective of the present work is to understand the operation of corporations in Brazil, as well as the question of possible abuse of voting rights by the controlling shareholder of publicly traded corporations and, consequently, knowledge of acts that configure it, as well as, the possible accountability for such an act. This objective is justified by the need to know the limits inherent in the role of controlling shareholder, as well as the means available and possible ways to hold them accountable, as far as their culpability. In order for the objectives and justifications to be properly justified, the methodology used is that of a bibliographical review, which will use books, scientific articles, Brazilian legislation and jurisprudential understandings that directly concern the proposed theme, seeking its understanding and the goals. As a result, it is intended to elucidate pertinent doubts to the subject and to understand the detailed operation of corporations